Degradation and impact of residual insecticide against important nuisance insect pest in soil. - Ab Majid, Abdul Hafiz (Universiti Sains Malaysia, 2016)
A study of degradation rate of various insecticides was conducted. Bifenthrin (soil treatment) showed the highest concentration of residue left in the soil after 36 months compared to fipronil and imidacloprid. It was supported by the bioassays where results showed that bioavailability of insecticides in soil was the greatest in bifenthrin, followed by fipronil and imidacloprid. For 12 months of treatment, chlorantraniliprole showed higher concentration of residue left in the soil compared to chlorpyrifos.